The Construction of Female Hero in Moana - Armyanti Aprellia (Passage, 2017)
Female hero is a type of character in literary works that differs from traditional female characters in literature, being portrayed as strong, smart and independent. An example of female hero is the main character of Disney film Moana. She is constructed using tools such as film elements and characterization. This research intends to see the process of how filmmakers construct the main character of Moana and what representation that is shown from that construction. The construction is analyzed based on the film techniques by Bordwell and Thompson (2008) and the methods of characterization by Boggs and Petrie (2008). Findings show that Moana is constructed as Female Hero mainly by framing and two aspect of mise-en-scène, which are costume and staging or performance, and two methods of characterization, which are external actions and foil character. It is shown that as a female hero, Moana is constructed as defying the traditional gender stereotype in literature and strengthening the portrayal of feminine power.Keywords: Construction, Female Hero, Film